Metaphor Counseling and Students Responsibility on Elementary School - Mashar, Riana; Nurihsan, Juntika (Universitas Muhammadiyah Metro, 2017)
The research aimed to figure out the effect of metaphor counseling in STAR KIDS (Story Teach Responsibility for Kids) module toward the responsibility of 6-7-year-old students of the first grade of elementary school. The research used untreated control group design by providing pretest and posttest sample design. The research subject consisted of 21 students in the experimental group and 26 students as the control group. The responsibility data collection performed by using observation guideline checklist, which quantified in the interval scale. SPM Raven scale measured the children's bits of intelligence. The STAR KIDS treatment is given in 15 meetings. The results of the pretest and posttest were analyzed by using Anacova analysis technique through SPSS 17 for Windows. The research result showed that (1) students of experiment group who received STAR KIDS metaphor counseling showed higher responsibility increase rather than students of a control group who did not receive the treatment, (2) The intelligence of the students did not show the effect on the effectiveness of counseling metaphor.